Aerobik dan Jus Tomat Dapat Menurunkan Tekanan Darah Penderita Hipertensi di Klinik Kartika 0730 Gunung Kidul Yogyakarta: Aerobic And Tomato Juice Can Lower Blood Pressure In Hypertension Patients at Kartika Clinic 0730 Gunung Kidul Yogyakarta - Itsni Azizatul Latifah; Nasiatul Aisyah Salim (Bachelor of Hospital Administration, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Introduction: Hypertension is recognized globally as a major public health problem. Antihypertensive drugs are effective in lowering blood pressure, but the achievement rate is still low worldwide. Although antihypertensive drugs can control blood pressure, low physical activity is a risk factor for hypertension mortality. Therefore, increasing physical activity through aerobic exercise is a recommendation for complementary therapy for the treatment of hypertension. Simultaneous implementation of moderate to high intensity exercise and weight loss through diet has been identified to be able to lower blood pressure more. And the content in tomatoes can lower blood pressure. Research Objective: This study aims to determine the effect of aerobics and the administration of tomato juice on reducing blood pressure in hypertensive patients at the Kartika Clinic 0730 Gunung Kidul Yogyakarta. Research Method: This research is a quantitative experimental study with a one group pretest-posttest design. The sample is 30 people with purposive sampling technique. The intervention was carried out 4 times for 2 weeks. Aerobic exercise is carried out for 30 minutes and 150 cc of tomato juice without sugar. Data analysis used paired t-test. Research Results: The results of the analysis show that there is an effect of aerobics and tomato juice on reducing blood pressure in hypertensive patients at the Kartika Clinic 0730 Gunung Kidul Yogyakarta. Conclusion: Aerobic exercise and giving tomato juice can reduce blood pressure in hypertension sufferers.